Student Action Recognition for Improving Teacher Feedback During Tele-Education - Dimitriadou, Eleni A.; Lanitis, Andreas (My University, 2023)
Strong interaction between instructors and students during online course delivery is essential for supporting the educational experience. As part of the efforts to maximise the interaction between educators and students, a pilot application that monitors the actions of the students in online courses while protecting as much as possible students' privacy was developed. The purpose of the present research is to determine whether the proposed application for monitoring is acceptable to the stakeholders involved in online classes and whether this application can contribute to the enhancement of the educational experience. As part of the research, the application was evaluated by 75 participants, which included students, parents, and educators, ensuring that the views of the main stakeholders in the educational process are considered. Before the intervention, an online questionnaire was completed by the participants, who then watched a video about the function of the application and/or used the actual application. After the intervention, the participants completed an online questionnaire with similar questions. The results indicate that the use of student action recognition systems is feasible in online courses and accepted by teachers, students and parents. Based on the results, most participants believe that the proposed application can contribute to the enhancement of the efficiency of distance education with regard to the student active participation, concentration level, learning results, teacher-student interaction, students' interest, and students' evaluation.
Keywords: Artificial intelligence; Education; Evaluation; Monitoring; Online courses; Privacy; Privacy protecting methods; Stakeholders; Student Action Recognition; Three-dimensional displays; Visualization